2016
DOI: 10.3390/brainsci6040055
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Cathodal Transcranial Direct Current Stimulation on Fear Memory in Healthy Human Subjects

Abstract: Background: Studies have demonstrated that fear memories can be modified using non-invasive methods. Recently, we demonstrated that anodal transcranial direct current stimulation (tDCS) of the right dorsolateral prefrontal cortex is capable of enhancing fear memories. Here, we examined the effects of cathodal tDCS of the right dorsolateral prefrontal cortex during fear reconsolidation in humans. Methods: Seventeen young, healthy subjects were randomly assigned to two groups, which underwent fear conditioning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
(44 reference statements)
0
22
5
Order By: Relevance
“…Previous literature showed increased vmPFC activity during classical extinction (17) but decreased when extinction occurs within the reconsolidation window (25). Whereas in our study we found that cathodal tDCS putatively occurring during the reconsolidation window, may reduce the fear index/avoidance tendency in the long-term, Mungee et al (21) found no effect for cathodal tDCS in SCRs. Whilst in our study we asked participants to verbally recall the CS+ followed by classical extinction (days 2 and 3), in Mungee et al (21) there was no information update because participants did not go through a complete extinction procedure following tDCS.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Previous literature showed increased vmPFC activity during classical extinction (17) but decreased when extinction occurs within the reconsolidation window (25). Whereas in our study we found that cathodal tDCS putatively occurring during the reconsolidation window, may reduce the fear index/avoidance tendency in the long-term, Mungee et al (21) found no effect for cathodal tDCS in SCRs. Whilst in our study we asked participants to verbally recall the CS+ followed by classical extinction (days 2 and 3), in Mungee et al (21) there was no information update because participants did not go through a complete extinction procedure following tDCS.…”
Section: Discussioncontrasting
confidence: 87%
“…Whereas in our study we found that cathodal tDCS putatively occurring during the reconsolidation window, may reduce the fear index/avoidance tendency in the long-term, Mungee et al (21) found no effect for cathodal tDCS in SCRs. Whilst in our study we asked participants to verbally recall the CS+ followed by classical extinction (days 2 and 3), in Mungee et al (21) there was no information update because participants did not go through a complete extinction procedure following tDCS. However, according to seminal studies, this new information is a necessary condition for the update of the CS+/US association (24).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…hyper-vigilance and excessive worrying). Thus, to eliminate the consolidated CR, extinction (the translational equivalent to exposure-based therapies) is implemented, consisting of consecutive presentations of the CS+ alone, leading to a new learning that inhibits the CS+/US association (18).By delivering tDCS to the right or left DLPFC to enhance fear extinction, researchers aimed to artificially modulate brain activity and decrease the fear response (19)(20)(21)(22). Counterintuitively, whereas previous studies have shown that tDCS using the anode electrode over the DLPFC leads to decreased fear, this gain was also associated with the adverse effect of decreasing stimuli discrimination (21,23).…”
mentioning
confidence: 99%